Understanding the persistence of vertical (stand-alone) HIV clinics in the health system in Uganda: a qualitative synthesis of patient and provider perspectives - Zakumumpa, Henry; Rujumba, Joseph; Kwiringira, Japheth; Kiplagat, Jepchirchir; Namulema, Edith; Muganzi, Alex (BMC health services research, 2018)
Although there is mounting evidence and policy guidance urging the integration of HIV services into general health systems in countries with a high HIV burden, vertical (stand-alone) HIV clinics are still common in Uganda. We sought to describe the specific contexts underpinning the endurance of vertical HIV clinics in Uganda. Methods: A qualitative research design was adopted. Semi-structured interviews were conducted with the heads of HIV clinics, clinicians and facility in-charges (n = 78), coupled with eight focus group discussions (64 participants) with patients from 16 health facilities purposively selected, from a nationally-representative sample of 195 health facilities across Uganda, because they run stand-alone HIV clinics. Data were analyzed by thematic approach as guided by the theory proposed by Shediac-Rizkallah & Bone (1998) which identifies; Intervention characteristics, organizational context, and broader environment factors as potentially influential on health programme sustainability. Results: Intervention characteristics: Provider stigma was reported to have been widespread in the integrated care experience of participating health facilities which necessitated the establishment of stand-alone HIV clinics. HIV disease management was described as highly specialized which necessitated a dedicated workforce and vertical HIV infrastructure such as counselling rooms. Organizational context: Participating health facilities reported health-system capacity constraints in implementing integrated systems of care due to a shortage of ART-proficient personnel and physical space, a lack of laboratory capacity to concurrently conduct HIV and non-HIV tests and increased workloads associated with implementing integrated care. Broader environment factors: Escalating HIV client loads and external HIV funding architectures were perceived to have perpetuated verticalized HIV programming over the past decade. Conclusion: Our study offers in-depth, contextualized insights into the factors contributing to the endurance of vertical HIV clinics in Uganda. Our analysis suggests that there is a complex interaction in supply-side constraints (shortage of ART-proficient personnel, increased workloads, laboratory capacity deficiencies) and demand-side factors (escalating demand for HIV services, psychosocial barriers to HIV care) as well as the specialized nature of HIV disease management which pose challenges to the integrated-health services agenda.
Keywords: Health systems; Service delivery; HIV; Implementation research; Antiretroviral therapy; Integration; Global health initiatives